Elective appendicectomy for chronic right lower quadrant pain: a clinical study - Maharaja, P.; Mohanty, Alok; Ganesh, T.; Baruah, Tridip Dutta; Smile, Robinson (International Surgery Journal, 2017)
Background: Chronic right-lower-quadrant abdominal pain is a frequent problem among growing population. The purpose of this study is to implement that persistent or recurrent right lower quadrant pain can be treated successfully by elective appendicectomy in properly selected cases. And to detail the outcome of management of these patients with appendectomy. Methods: This observational study was done in Mahatma Gandhi Medical College and Research Institute, Pondicherry, India between 2014-16 in patients with clinical diagnosis of chronic RLQ pain and undergoing appendicectomy. Routine laboratory investigations included hemoglobin percentage, serum leukocyte count and differential count, ESR, urine microscopy, random blood sugar, blood urea, serum creatinine, abdominal ultrasound (USG), and histopathological examination (HPE) of removed the appendix. The primary outcome measure was pain scored by the patient at 6th week and 12th week after surgery. Postoperative histopathology report was compared with the clinical improvement. The analysis of primary outcome was performed on an intention-to-treat basis. P<0.050 was considered statistically significant. Results: Eighty-two cases of chronic RLQ pain, who met the inclusion criteria, were included in the clinical study. Elective appendicectomy was performed in all 82 patients and sample analysed by HPE. Out of 82 (100 %) patients who underwent appendicectomy, 45 (54.90 %) were male and 37 (45.10 %) were female. About 79 cases (96.34%) of the patients were completely pain free, and only 3 (3.66%) patients did not improve after elective appendicectomy. There was no mortality. Out of 82 patients, 52 (63.41%) patients had pathological signs of appendicitis and 30 (36.59 %) patients showed the normal appendix. Conclusions: Elective laparoscopic appendicectomy in patients with chronic RLQ pain may be an effective therapeutic procedure in properly selected cases. Histopathology of the removed appendix does not contribute to the diagnosis. However, there appears to be definite scope for a much longer duration of follow-up study of the patients with chronic RLQ pains.